Influence of brush type as a carrier of adhesive solutions and paper points as an adhesive-excess remover on the resin bond to root dentin - Souza, Rodrigo O.A. [UNESP]; Lombardo, Geraldo H.L. [UNESP]; Michida, Silvia M.A. [UNESP]; Galhano, Graziela [UNESP]; Bottino, Marco Antônio [UNESP]; Valandro, Luiz Felipe [UNESP] (My University, 2007)
Purpose: To evaluate the influence of the brush type as a earner of priming adhesive solutions and the use of paper points as a remover of the excess of these solutions on the push-out bond strength of resin cement to bovine root dentin. The null hypotheses were that brush type and the use of paper points do not affect the bond strength. Materials and Methods: The canals of 80 single-root bovine roots (16 mm in length) were prepared at 12 mm using the preparation drill (FRC Postec Plus, Ivoclar). Half of each root was embedded in acrylic resin and the specimens were divided into 8 groups, considering the factors brush type (4 levels) and paper point (2 levels) (n = 10): Gr 1: small microbrush (Cavi-Tip, SDI); Gr 2: Microbrush (Dentsply); Gr 3: Endobrush (Bisco); Gr 4: conventional brush (Bisco); Gr 5: Cavi-Tip (SDI) + paper points; Gr 6: Microbrush (Dentsply) + paper points; Gr 7: Endobrush (Bisco) + paper points; Gr 8: conventional brush (Bisco) + paper points. The root dentin was treated with a multistep total-etch adhesive system (All Bond 2). The adhesive system was applied using each microbrush, with and without using paper points. One fiber post was molded with addition silicon and 80 posts were made of resin cement (Duolink), The resin posts were luted (Duolink resin cement), and the specimens were stored for 24 h in water at 37°C. Each specimen was cut into 4 disk-shaped samples (1.8 mm in thickness), which were submitted to the push-out test. Results: The brush type (p < 0.0001) (small microbrush > microbrush = endobrush = conventional brush) and the use of paper points (p = 0.0001) (with > without) influenced the bond strength significantly (two-way ANOVA). The null hypotheses were rejected. Conclusion: The smallest brush (Cavi-Tip) and the use of paper points significantly improved the resin bond to bovine root dentin.
Keywords: Bond strength; Microbrush; Paper point; Push-out test; Resin cement; Root canal dentin; All Bond 2; All-Bond 2; dentin bonding agent; Duo Link; Duo-Link; methacrylic acid derivative; resin cement; silicone derivative; unclassified drug; water; animal; cattle; chemistry; dental acid etching; dental bonding; dentin; endodontics; equipment design; instrumentation; materials testing; mechanical stress; methodology; paper; scanning electron microscopy; surface property; temperature; time; tooth crown; tooth pulp; ultrastructure; Acid Etching, Dental; Animals; Cattle; Dental Bonding; Dental Pulp Cavity; Dentin; Dentin-Bonding Agents; Equipment Design; Materials Testing; Methacrylates; Microscopy, Electron, Scanning; Paper; Post and Core Technique; Resin Cements; Root Canal Preparation; Silicones; Stress, Mechanical; Surface Properties; Temperature; Time Factors; Water